1988
DOI: 10.1093/ajcn/48.4.980
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of serum lipids and its relation to diet in an elderly institutionalized population

Abstract: This study was conducted to determine the nutritional status with respect to fatty acids of 53 institutionalized elderly subjects (group A). Seven-day food records and biochemical determinations were used. The same protocol was applied to 25 healthy young adults (group B). The 1981 French Recommended Dietary Allowances were used to assess adequacy of intake. Total fat intake was found to be too high in both groups. Higher intakes of animal fats and saturated fatty acids and lower intakes of polyunsaturated fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 27 publications
6
30
1
3
Order By: Relevance
“…These data are in agreement with two studies in hospitalised patients (Holman, 1979;Lecerf et al, 1993), although lower percentages of 20:4 n-6 were observed in PL from elderly hospitalised patients in another study (Asciutti-Moura, 1988). The data of our study suggest that in our cohort of elderly women living at home, the 20:4 n-6 dietary supply compensated both the lower 18:2 n-6 intake and possibly some weakness of the n-6 biosynthetic pathway.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These data are in agreement with two studies in hospitalised patients (Holman, 1979;Lecerf et al, 1993), although lower percentages of 20:4 n-6 were observed in PL from elderly hospitalised patients in another study (Asciutti-Moura, 1988). The data of our study suggest that in our cohort of elderly women living at home, the 20:4 n-6 dietary supply compensated both the lower 18:2 n-6 intake and possibly some weakness of the n-6 biosynthetic pathway.…”
Section: Discussionsupporting
confidence: 93%
“…The same tendency was also detected in institutionalised patients: lower DHA percentages in PL were found in elderly patients than in a control group but, again, the difference was not signi®cant (Asciutti-Moura et al, 1988). Striking differences, however, appeared in the DHA EPAa18:3 n-3 ratio, which has been proposed to identify blocks in the n-3 pathway activity (Siguel & Maclure, 1987), and also in the DHAaEPA ratio, more speci®cally concerning the last steps of DHA biosynthesis.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In humans, the liver desaturation activities are much lower than in rats Blond et al, 1981 Despite that, several studies have shown that few differences exist between elderly and young subjects with respect to the n-6 and n-3 fatty acid content of serum (Holman et al, 1979;Asciutti-Moura et al, 1988), erythrocyte (Driss et al, 1988) and platelet (Vericel et al, 1988) From these data, it is evident that longchain essential n-6 fatty acids were oxidized to C0 2 at a very low rate, much lower than the 'parents' 18:2n-6 and 18:3n-3. This is evidence that when provided as very longchain fatty acids, the EFA are required in lower amount in the diet than the precursors 18:2n-6 and 18:3n-3.…”
Section: Dietary Sources Of Essential Fatty Acidsmentioning
confidence: 99%